Tissue engineering in plastic and reconstructive surgery: fostering advances in the 21st century via an understanding of the present state of the art and future possibilities - Manish Anand; Manish Bhagania; Kiranmeet Kaur (Archives of Aesthetic Plastic Surgery, 2023)
Tissue engineering is a subfield of regenerative medicine that has been hailed as the most cutting-edge medical and surgical achievement to date. Tissue engineering aims to restore or construct whole tissues that have been lost due to congenital disabilities, trauma, or surgery. Tissue engineering is based on the premise of obtaining mesenchymal stem cells that can be used to create an embryologically comparable organ. To regenerate an organ that resembles the intended tissue to be replaced, a complex synergistic interplay between stem cells, signaling molecules, and scaffold, is required. Tissue engineering in plastic surgery is expected to reduce surgical morbidity by integrating cell signals or bio-artificial components taken from the patient’s cells, which may replace damaged bodily tissue without the need for extensive reconstructive surgery. With the advent of 3-dimensional printers for modeling scaffolds and current tissue engineering methods for the regeneration of muscle, bone, and cartilage in the laboratory, the scope of tissue engineering is no longer confined to cells and scaffolds, but also encompasses growth factors and cytokines. Although these methods seem promising, clinical success has been limited to essential tissue regeneration, with considerable difficulties remaining to overcome. This paper aims to introduce readers to tissue engineering’s existing breadth, regeneration processes, limits, and prospects.